The Ultimate Guide to Informed Wearable Technology: A hands-on approach for creating wearables from prototype to purpose using Arduino systems - Farion, Christine (Packt Publishing, 2022)
Master wearable technology with this book including colored images and over 50 activities using Arduino and ESP32, build useful, stylish, and smart wearable devices, and create interactive circuits that react to us and our environment Key Features Learn wearable technology and build electronic circuits with fun activities using Arduino systemsGet an in-depth understanding of e-textiles and ESP32 microcontrollers to create interactive wearablesApply a design innovation approach and best practices to address real-world issues Book Description Wearable circuits add interaction and purpose to clothing and other wearable devices that are currently widely used in medical, social, safety, entertainment, and sports fields. To develop useful and impressive prototypes and wearables, you’ll need to be skilled in designing electronic circuits and working with wearable technologies. This book takes you on an interesting journey through wearable technology, starting from electronic circuits, materials, and e-textile toolkits to using Arduino, which includes a variety of sensors, outputs, actuators, and microcontrollers such as Gemma M0 and ESP32. As you progress, you’ll be carefully guided through creating an advanced IoT project. You’ll learn by doing and create wearables with the help of practical examples and exercises. Later chapters will show you how to develop a hyper-body wearable and solder and sew circuits. Finally, you’ll discover how to build a culture-driven wearable to track data and provide feedback using a Design Innovation approach. After reading this book, you’ll be able to design interactive prototypes and sew, solder, and program your own Arduino-based wearable devices with a purpose. What you will learn Construct sewable electronic circuits with conductive thread and materialsDiscover the features of LilyPad, Gemma, Circuit Playground, and other boardsUse various components for listening, moving, sensing actions, and visualizing outputsControl ESP32 development boards for IoT explorationUnderstand why and how to prototype to create interactive wearablesGet skilled in sewing and soldering sensors to Arduino-based circuitsDesign and build a hyper-body wearable that senses and reactsMaster a Design Innovation approach for creating wearables with a purpose Who this book is for This book is for electronics engineers, embedded system engineers and designers, and R&D engineers, who are beginners in the wearable technology domain as well as makers and hobbyists who have an interest in creative computing. It will also be useful for teachers, students, and researchers, who are learning interaction design, physical computing, technology, fashion, or arts. Having a basic understanding of Arduino-based systems will help in easily comprehending the contents of the book.